Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae) - Ning, Xin; Kompier, Tom; Yu, Xin; Bu, Wenjun (Zootaxa, 2016)
One new species of Paracercion Weekers and Dumont, 2004 (Paracercion ambiguum Kompier & Yu, 2016, holotype male, Vietnam, Lang Son province, Huu Lien Nature Reserve, 1-XII-2013, deposited in Institute of Entomology, College of Life Sciences of Nankai University, Tianjin, China) is proposed on the basis of molecular and morphological evidence. A COI gene tree is presented for Paracercion species and several morphologically related genera. The species is described and illustrated for both sexes. Diagnostic figures of the genital ligula and caudal appendages are provided.